Investigation of the relevant kinetic processes in the initial stage of a double-arcing instability in oxygen plasmas - Mancinelli, Beatriz Rosa (2018)
A numerical investigation of the kinetic processes in the initial (nanosecond range) stage of the double-arcing instability was developed. The plasma-sheath boundary region of an oxygen-operated cutting torch was considered. The energy balance and chemistry processes in the discharge were described. It is shown that the double-arcing instability is a sudden transition from a diffuse (glow-like) discharge to a constricted (arc-like) discharge in the plasma-sheath boundary region arising from a field-emission instability. A critical electric field value of ∼10^7 V/m was found at the cathodic part of the nozzle wall under the conditions considered. The field-emission instability drives in turn a fast electronic-to-translational energy relaxation mechanism, giving rise to a very fast gas heating rate of at least ∼10^9 K/s, mainly due to reactions of preliminary dissociation of oxygen molecules via the highly excited electronic state O2(B^3) populated by electron impact. It is expected that this fast oxygen heating rate further stimulates the discharge contraction through the thermal instability mechanism.